2022
DOI: 10.3390/foods11091198
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Fruits and Vegetables Based on Spatially Resolved Spectroscopy: A Review

Abstract: Damage occurs easily and is difficult to find inside fruits and vegetables during transportation or storage, which not only brings losses to fruit and vegetable distributors, but also reduces the satisfaction of consumers. Spatially resolved spectroscopy (SRS) is able to detect the quality attributes of fruits and vegetables at different depths, which is of great significance to the quality classification and defect detection of horticultural products. This paper is aimed at reviewing the applications of spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…Color changes can be caused by the tissue structure [15]. Relationships between firmness, tissue microstructure, and optical properties during storage were confirmed and it was reported that optical properties can be used to evaluate the changes in fruit microstructure during post-harvest storage [16,17].…”
Section: Introductionmentioning
confidence: 84%
“…Color changes can be caused by the tissue structure [15]. Relationships between firmness, tissue microstructure, and optical properties during storage were confirmed and it was reported that optical properties can be used to evaluate the changes in fruit microstructure during post-harvest storage [16,17].…”
Section: Introductionmentioning
confidence: 84%
“…With the rapid development of deep learning [ 34 , 35 ], recent years have witnessed a rapid rise in the growth of the deep-learning-based SR methods. As a pioneer work, Dong et al [ 23 ] first proposed SRCNN.…”
Section: Related Workmentioning
confidence: 99%
“…( Metlenkin et al., 2022 ) distinguished Hass avocado fruits by defects using hyperspectral imaging (HSI). The question revolves around the practical utilization of these approaches and the challenges associated with improving data processing speed and in-line implementation ( Cortés et al., 2019 ; Si et al., 2022 ). Quick hardware and software are required to fulfill the demands of swift analysis for extensive hyperspectral datasets ( Xu et al., 2023 ) and machine learning algorithms, especially those relying on deep learning act as black boxes rather than using interpretability models for high-stakes decisions ( Caceres-Hernandez et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%